2003
DOI: 10.1021/np020576x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Novel Polyphenols from the Fruit of Manilkara zapota (Sapodilla)

Abstract: Activity-guided fractionation of a methanol extract from the fruit of Manilkara zapota cv. Tikal resulted in the isolation of two new antioxidants, methyl 4-O-galloylchlorogenate (1) and 4-O-galloylchlorogenic acid (2), along with eight known polyphenolic antioxidants, namely, methyl chlorogenate (3), dihydromyricetin (4), quercitrin (5), myricitrin (6), (+)-catechin (7), (-)-epicatechin (8), (+)-gallocatechin (9), and gallic acid (10). Of the 10 polyphenols, 1 showed the highest antioxidant activity (IC(50) =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
1
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(134 citation statements)
references
References 20 publications
3
121
1
9
Order By: Relevance
“…This glycosilated flavonol was also found in the fruits of Pouteria Aubl. (Sapotaceae; Ma et al, 2004) and of Manilkara zapota (L.) P. Royen (Sapotaceae; Ma et al, 2003). In addition, it was also isolated in the leaves Eugenia L. (Myrtaceae; Schmeda-Hirschmannet et al, 1987) and in the latex of Croton draco Schltdl.…”
Section: Flavonoidsmentioning
confidence: 98%
“…This glycosilated flavonol was also found in the fruits of Pouteria Aubl. (Sapotaceae; Ma et al, 2004) and of Manilkara zapota (L.) P. Royen (Sapotaceae; Ma et al, 2003). In addition, it was also isolated in the leaves Eugenia L. (Myrtaceae; Schmeda-Hirschmannet et al, 1987) and in the latex of Croton draco Schltdl.…”
Section: Flavonoidsmentioning
confidence: 98%
“…Ethanol pulp extract contains alkaloids, saponins, terpenoids, flavonoids, tannins, leucoanthocyanidins, anthroquinones, glucosides and catechol (Gomathy et al 2013). Ma et al (2003) found bioactive flavonoids from methanol extract of sapota fruit such as (À)-epicatechin, (+)-gallocatechin, gallic acid, quercetin, myricitrin and (+)-catechin, of which the latter three pure compounds were reported to inhibit enzyme collagenase and elastase activities (Sim et al 2007;Thring et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, flavonoids could also induce mechanisms that may kill cancer cells and inhibit tumor invasion (Lotito, Frei, 2006). On the other hand, it has been reported that the major constituents isolated from fruits of Manilkara zapota are polyphenols (methyl chlorogenate, dihydromyricetin, quercitrin, myricitrin, (+)-catechin, (-)-epicatechin, (+)-gallocatechin, and gallic acid (Ma et al, 2003). The inhibitory properties of EEFM against EAC may be due to the presence of these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Previous phytochemical investigations on the leaves of this plant have resulted in the isolation of lupeol acetate, oleanolic acid, apigenin-7-O-α-Lrhamnoside, myricetin-3-O-α-L-rhamnoside and caffeic acid (Fayek et al, 2012). Moreover, the major constituents isolated from fruits of Manilkara zapota are polyphenols (methyl chlorogenate, dihydromyricetin, quercitrin, myricitrin, (+)-catechin, (-)-epicatechin, (+)-gallocatechin, and gallic acid (Ma et al, 2003). But no studies to date have been conducted to demonstrate the antitumour activity of Manilkara zapota fruit.…”
Section: Introductionmentioning
confidence: 99%